Reader's Digest : Did You Know? New insights into a world that is full of astonishing facts and astounding stories. - Amrine, Douglas; Reader's Digest (London, The Reader's Digest Association Limited, 1997)
Presents information on a wide variety of topics.
Keywords: Encyclopedia